Forged in fire - Warren, Linda (Colton 911: Chicago., 2021)
"Is Lila Colton a thief? Insurance investigator Carter Finch vows to uncover the truth when he visits her gallery. But his temporary mission goes awry when Lila turns out to be incredibly beautiful...and just a bit lethal. A fire engulfs the building, which puts them both in harm's way. Is Lila his ally or pushing him into a deadly trap?"--